Efficacy of nanocrystalline bone substitute biphasic calcium phosphate/poly-DL-lactide-co-glycolide for periodontal intrabony defects filling - Stevanović Momir; Biočanin Vladimir; Nedić Milica; Ignjatović Nenad (Vojnosanitetski Pregled)
Background/Aim. Different bone substitutes have been used for filling and reparation of intrabony defects. The aim of this study was to compare nanocrystalline material, biphasic calcium phosphate poly-DL-lactide-co-glycolide (BCP/PLGA) with deproteinised bovine bone (DPBB) and β-tricalcium phosphate (β- TCP) in the treatment of periodontal intrabony defects. Methods. The study included 24 patients with bilateral, intrabony defects in the region of the upper first and second premolar, and the upper first molar. On one side of the mouth, DPBB (BioOss®) was used to fill defects in upper premolars while β- TCP (RTR®) was used for the upper first molar. BCP/PLGA was applied into periodontal defects of the upper premolars and upper first molar of the opposite side. Results. The comparison of the BCP/PLGA and the β-TCP group, 6 months following filling of defects, showed a statistically significant reduction of periodontal pocket depth (PPD) and the position of the cementenamel junction (CEJ) in the group with BCP/PLGA, when compared to the β-TCP group. The reduction of PPD and CEJ was similar in the groups treated with BCP/PLGA and DPBB. Conclusion. Significant reductions of PPD and CEJ were registered in the group with BCP/PLGA when compared to the β- TCP group. [Projekat Ministarstva nauke Republike Srbije, br. 175021 i br. III45004]